An update on the use of pharmacotherapy for opioid-induced bowel dysfunction. (11th February 2023) - Mousavi, Taraneh; Nikfar, Shekoufeh; Abdollahi, Mohammad
ABSTRACT: Introduction: With the growing rate of aging and the incidence of chronic diseases, there has been an upsurge in opioid prescription and abuse worldwide. This has been associated with increased reports of opioid-related adverse events, particularly opioid-induced bowel dysfunction (OIBD), calling for a rational clinical management strategy. Areas Covered: Through searching PubMed, Scopus, Cochrane Library, and Web of Science, English literature was gathered as of 1 January 2017. Furthermore, the USFDA, EMA, TGA, Clinicaltrials.Gov, WHO-ICTRP databases, and the latest guidelines were reviewed to extract ongoing clinical studies and provide an evidence-based expert opinion with detailed information on efficacy, safety, approval status, and pharmacokinetics of the currently used medications. Expert opinion: Despite the significant burden of OIBD, the clinical development of agents lags behind disease progress. Although in most places, management of opioid-induced constipation (OIC) is initiated by lifestyle modifications followed by laxatives, opioid antagonists, and secretagogue agents, there are still major conflicts among global guidelines. The fundamental reason is the lack of head-to-head clinical trials providing inter- and intragroup comparisons between PAMORAs, laxatives, and secretagogue agents. These investigations must be accompanied by further valid biopharmaceutical and economic evaluations, paving the way for rational clinical judgment in each context.